The impact of self-employment on the economic integration of immigrants: Evidence from Germany - Jan Brzozowski; Anke Lasek (Journal of Entrepreneurship, Management and Innovation)
Traditional approaches in migration studies suggest that self-employment and entrepreneurial activities enhance the perspectives of economic advancement of immigrants in host countries. Therefore, in many popular destinations in Western Europe and Northern America, policies encouraging the self-employment of immigrants have been proposed. But does the self-employment contribute to the economic integration of immigrants? Is it a universal, one-way avenue that guarantees the successful insertion of foreigners in a new socio-economic environment? Based on the German Socio-Economic Panel dataset, this study empirically investigates the effect of self-employment on the economic integration of immigrants in one of the most important host countries in Europe. Our results demonstrate that the current self-employment status in Germany is associated with higher income in absolute and relative (self-assessment) terms. The immigrants with previous self-employment experience in Germany are less integrated than the average. This result indirectly shows that the business economy of immigrants is associated with a high risk of failure and not all self-employed individuals succeed in advancing in economic terms in a host country. Consequently, we argue that host countries should be more cautious in promoting entrepreneurship as the “perfect” and “universal” strategy that improves economic integration.